Intimate enemies : translation in francophone contexts - Batchelor, Kathryn; Bisdorff, Claire, 1981- (Francophone postcolonial studies, 2013)
The concept of translation has become central to postcolonial theory in recent decades. This volume draws together reflections by translators, authors and academics working across Africa, the Caribbean and the Indian Ocean - areas where the linguistic legacies of French colonial operations are long-lasting and complex.